The public health crisis of underimmunisation: a global plan of action. Issue 1 (January 2020) - Gostin, Lawrence O; Hodge, James G; Bloom, Barry R; El-Mohandes, Ayman; Fielding, Jonathan; Hotez, Peter; Kurth, Ann; Larson, Heidi J; Orenstein, Walter A; Rabin, Kenneth; Ratzan, Scott C; Salmon, Daniel
Summary: Vaccination is one of public health's greatest achievements, responsible for saving billions of lives. Yet, 20% of children worldwide are not fully protected, leading to 1·5 million child deaths annually from vaccine-preventable diseases. Millions more people have severe disabling illnesses, cancers, and disabilities stemming from underimmunisation. Reasons for falling vaccination rates globally include low public trust in vaccines, constraints on affordability or access, and insufficient governmental vaccine investments. Consequently, an emerging crisis in vaccine hesitancy ranges from hyperlocal to national and worldwide. Outbreaks often originate in small, insular communities with low immunisation rates. Local outbreaks can spread rapidly, however, transcending borders. Following an assessment of underlying determinants of low vaccination rates, we offer an action based on scientific evidence, ethics, and human rights that spans multiple governments, organisations, disciplines, and sectors.